2015
DOI: 10.1007/s00122-015-2641-7
|View full text |Cite
|
Sign up to set email alerts
|

QTL detection for wheat kernel size and quality and the responses of these traits to low nitrogen stress

Abstract: QTLs for tolerance to N stress, 27 and 14 of which were stable across the tested environments, respectively. These QTLs were distributed across all wheat chromosomes except for chromosomes 3A, 4D, 6D, and 7B. Eleven QTL clusters that simultaneously affected kernel size-and quality-related traits were identified. At nine locations, 25 of the 49 QTLs for N deficiency tolerance coincided with the QTLs for kernel characteristics, indicating their genetic independence. The feasibility of indirect selection of a sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 63 publications
(119 reference statements)
12
62
0
Order By: Relevance
“…Similarly, Maccaferri et al [6] identified one MTA on 7AL and 7BL in durum wheat. MTAs on chromosomes 7 have been also found in bread wheat [68, 86] and in a mapping population from wild emmer and durum wheat [46, 54]. It is remarkable that the QTLs conferring improved TKW on chromosome 7B have been co-localized with QTLs conferring higher grain yield [46].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Maccaferri et al [6] identified one MTA on 7AL and 7BL in durum wheat. MTAs on chromosomes 7 have been also found in bread wheat [68, 86] and in a mapping population from wild emmer and durum wheat [46, 54]. It is remarkable that the QTLs conferring improved TKW on chromosome 7B have been co-localized with QTLs conferring higher grain yield [46].…”
Section: Discussionmentioning
confidence: 99%
“…The nitrogen treatments, field arrangements and experimental designs of the ten environments were performed as described previously 3, 68, 69 .…”
Section: Methodsmentioning
confidence: 99%
“…Suggestive QTLs with an average LOD value >3.0 in a dataset were noted. A QTL with an average LOD value > 3.0 and average phenotypic variance contribution > 10% was defined as a major QTL [55,56]. The QTLs in the present study were compared with previously published ones [2,21,31,32].…”
Section: Linkage Mapmentioning
confidence: 98%